Iron runner castable containing pre-synthesized EG-SiC and preparation method thereof

By introducing pre-synthetic EG-SiC into the iron groove material, nano-silicon carbide whiskers grown between the worm-like expanded graphite sheet structures are used to form a heterogeneous network structure with high specific surface area, and carbon in the existing iron groove material is solved The problem of difficulty in forming ceramic reinforced phases is difficult to source selection, which significantly improves slag resistance and high-temperature mechanical properties.

CN119390460AActive Publication Date: 2025-02-07WUHAN METALLURGY ARCHITECTURE RES YUAN CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411539266.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-07
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

It is difficult to form ceramic reinforced phases at high temperatures in existing iron groove materials, resulting in insufficient slag resistance and high temperature mechanical properties.

Method used

Pre-synthetic EG-SiC is used to grow nanosilicon carbide whiskers in situ between worm-like expanded graphite sheet structures to form a heterogeneous network structure with high specific surface area, improving the early binding strength and slag resistance of iron groove castables.

Benefits of technology

The slag resistance and high temperature mechanical properties of iron groove castable are significantly improved, and the resistance to thermal stress damage is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005112375810000061
    Figure BDA0005112375810000061
  • Figure HDA0005112375830000011
    Figure HDA0005112375830000011
  • Figure HDA0005112375830000012
    Figure HDA0005112375830000012
Patent Text Reader

Abstract

The invention discloses an iron runner castable containing pre-synthesized EG-SiC and a preparation method of the iron runner castable, and belongs to the technical field of amorphous refractory castable. The iron runner castable is prepared from the following raw materials in percentage by mass: 10 to 17 weight percent of tabular corundum, 7 to 13 weight percent of composite micro powder, 12 to 25 weight percent of silicon carbide, 1 to 3 weight percent of calcium aluminate cement, 1 to 3 weight percent of spherical asphalt, 0.1 to 0.2 weight percent of explosion-proof fiber, 2 to 5 weight percent of composite additive and the balance of brown aluminum oxide particles, 1 to 3 weight percent of pre-synthesized EG-SiC is additionally added; wherein the pre-synthesized EG-SiC is formed by in-situ growth of nano silicon carbide whiskers between vermicular expanded graphite lamellar structures. The iron runner castable is high in early bonding strength, the slag resistance of the iron runner castable is remarkably improved, the high-temperature mechanical property and the thermal stress damage resistance of the material are improved, and the iron runner castable has important application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of amorphous refractory castables, and in particular relates to an iron channel castable containing pre-synthesized EG-SiC and a preparation method thereof. Background Art

[0002] Iron tapping from the iron ditch is an important part of the blast furnace ironmaking process. In order to ensure the safe and efficient operation of the process, extremely high requirements are placed on the refractory materials used in the iron ditch. Currently, the commonly used refractory materials for the iron ditch are alumina-silicon carbide-carbon iron ditch castables. Among them, carbon materials have become an important component of iron ditch materials due to their high thermal conductivity, low expansion and poor wetting with slag. They can not only improve the thermal shock stability of iron ditch materials, but also improve their resistance to slag erosion. Currently, the commonly used carbon sources in iron ditch materials include spherical asphalt, carbon black, graphite, carbon nanotubes, etc., which are generally added in the form of a composite of multiple carbon sources. Each carbon source has its advantages and disadvantages. Spherical asphalt is easier to add to the castable due to its spherical shape, but it contains certain volatiles; flake graphite is a graphitized carbon source, but it is not easy to disperse in the castable because it is not wetted by water; in comparison, expanded graphite has a worm-like structure and is easier to disperse, but its reaction activity is low at high temperatures and it is difficult to form a ceramic reinforcement phase; carbon nanotubes have excellent high-temperature performance, but they are more difficult to disperse than micron carbon sources. Therefore, how to choose a suitable carbon source to play a better role in iron channel materials is a top priority. Summary of the invention

[0003] The purpose of the present invention is to provide an iron ditch castable containing presynthesized EG-SiC and a preparation method thereof. The iron ditch castable has high early bonding strength, significantly improves the slag resistance of the iron ditch castable, and improves the high temperature mechanical properties and the ability to resist thermal stress damage of the material, and has important application prospects.

[0004] In order to achieve the above-mentioned invention object, the present invention adopts the following technical solutions:

[0005] Provided is an iron ditch castable containing presynthesized EG-SiC, wherein the raw materials are composed of: 10-17wt% of plate-shaped corundum, 7-13wt% of composite micropowder, 12-25wt% of silicon carbide, 1-3wt% of calcium aluminate cement, 1-3wt% of spherical asphalt, 0.1-0.2wt% of explosion-proof fiber, 2-5wt% of composite additives, and the balance is brown corundum particles; 1-3wt% of presynthesized EG-SiC is added; wherein:

[0006] The pre-synthesized EG-SiC is nanometer silicon carbide whiskers grown in situ between worm-like expanded graphite sheet structures.

[0007] According to the above scheme, the preparation of the pre-synthesized EG-SiC comprises the following steps:

[0008] Expanded graphite (EG) is placed in a nickel acetate solution, and then filtered and dried after ultrasonic stirring and dispersion to obtain expanded graphite loaded with a nickel acetate catalyst; then the expanded graphite loaded with the nickel acetate catalyst is placed in a microwave reactor, and nitrogen gas carries a mixed vapor of anhydrous ethanol and methylsilane into the microwave reactor for microwave heating reaction to prepare pre-synthesized EG-SiC.

[0009] Preferably, the nickel acetate solution contains Ni 2+ The concentration is 0.05-0.25 mol / L; preferably 0.15-0.25 mol / L.

[0010] Preferably, the drying process is: drying at 60-80° C. for 8-12 hours.

[0011] Preferably, the ultrasonic stirring time is 15-30 min.

[0012] Preferably, the volume ratio of anhydrous ethanol to methylsilane is 1-2:1.

[0013] Preferably, the mixed steam is carried into the microwave reactor by nitrogen gas by inserting a nitrogen vent pipe into a mixed solution of anhydrous ethanol and methylsilane at 80-90°C.

[0014] Preferably, the microwave heating reaction is carried out at 1100-1200°C for 20-45 min; more preferably, the microwave heating power is 700-1100W.

[0015] Preferably, the flow rate of nitrogen is controlled at 200-500 mL / min.

[0016] According to the above scheme, the content of Al2O3 in the plate-like corundum is >99wt%, and the particle size is 1-0.1mm and <45μm.

[0017] According to the above scheme, the composite micropowder is a composite of two or more of ordinary silicon micropowder, high-purity silicon micropowder and active α-Al2O3 micropowder, wherein: the content of SiO2 in the ordinary silicon micropowder is >95wt%, and the particle size is <0.5μm; the content of SiO2 in the high-purity silicon micropowder is >99wt%, and the particle size is <0.5μm; the content of Al2O3 in the active α-Al2O3 micropowder is >99.5wt%, and the particle size is <5μm.

[0018] Preferably, it contains at least ordinary silicon powder or high-purity silicon powder.

[0019] According to the above scheme, the content of SiC in the silicon carbide is >98wt%, and the particle size is 1-0.1mm and <75μm.

[0020] According to the above scheme, the content of Al2O3 in the calcium aluminate cement is >70wt% and the particle size is <45μm.

[0021] According to the above scheme, the composite additive is a composite of at least two of boron carbide, silicon powder, zirconium boride, metal aluminum powder, and polycarboxylic acid dispersant. Preferably, at least silicon powder is contained.

[0022] According to the above scheme, the content of Al2O3 in the brown corundum particles is >95wt%, and the particle sizes include 3-1mm, 5-3mm, and 8-5mm.

[0023] According to the above scheme, the particle size of the spherical asphalt is 1-0mm.

[0024] Also provided is a method for preparing an iron ditch castable containing pre-synthesized EG-SiC, comprising the following steps:

[0025] Weigh raw materials of plate-shaped corundum, composite micropowder, silicon carbide, calcium aluminate cement, presynthesized EG-SiC, spherical asphalt, explosion-proof fiber, composite additives and brown corundum particles and mix them evenly, add 3-6wt% of water in the total amount of the raw materials and mix them evenly, then cast and vibrate to obtain iron ditch castable.

[0026] According to the above scheme, the castable is also cured and dried at room temperature, cured at room temperature for 20-28 hours, and dried at 100-120°C for 20-28 hours after demoulding.

[0027] The present invention provides an iron ditch castable containing presynthesized EG-SiC, which introduces presynthesized EG-SiC, and nanometer silicon carbide whiskers are uniformly grown in situ between worm-like expanded graphite lamellar structures, which have extremely high specific surface area, can induce the formation of cement hydration phase at low temperature, improve the early bonding strength of the iron ditch castable, and simultaneously form an inlaid structure of aluminum silicate and carbonaceous raw materials, which can significantly improve the slag resistance of the iron ditch castable. In addition, the presynthesized EG-SiC is an expanded graphite-silicon carbide whisker heterogeneous network structure, and the silicon carbide whiskers are embedded in the pores of the matrix to form a new type of strengthening and toughening structure, and the expanded graphite plays a toughening role by playing a lamellar structure slip mechanism, while a large number of silicon carbide whiskers dispersed at the tip are effectively strengthened, which significantly improves the high-temperature mechanical properties of the material and the ability to resist thermal stress damage.

[0028] Furthermore, in the process of preparing EG-SiC, first, nickel acetate is used as a catalyst, and expanded graphite is immersed in a nickel acetate solution for loading, so that nickel acetate is more evenly dispersed on the surface of expanded graphite, which is conducive to the final generation of uniform silicon carbide whiskers. Secondly, the mixed steam of anhydrous ethanol and methylsilane is subjected to microwave heating reaction with the expanded graphite loaded with nickel acetate catalyst, and the reducing atmosphere of ethanol decomposition effectively inhibits the agglomeration and growth of nano-nickel particles, avoiding the rapid growth of nickel oxide formed by traditional inorganic nickel salts during the heating process, and ensuring the catalytic efficiency; at the same time, methylsilane provides an effective silicon source for chemical vapor deposition, and ethanol decomposition hydrocarbon gas is used as a carbon source, and uniform silicon carbide whiskers are finally generated under the action of the catalyst on the surface of expanded graphite.

[0029] Furthermore, during the heat treatment process, the residual catalyst in the pre-synthesized EG-SiC will also promote the reaction between elemental silicon and silicon powder (promoting the formation of silicon monoxide vapor at high temperature) in the iron ditch castable and CO, strengthening the heterogeneous network structure of expanded graphite-silicon carbide whiskers and further improving the performance of the iron ditch castable.

[0030] The beneficial effects of the present invention are as follows:

[0031] 1. The invention provides an iron ditch castable containing presynthesized EG-SiC. By introducing the presynthesized EG-SiC, silicon carbide whiskers are uniformly dispersed on expanded graphite, which is easy to disperse in the iron ditch castable, and the content of small-sized silicon carbide whiskers in the iron ditch castable is significantly increased; at the same time, the high specific surface area is used to induce cement hydration behavior to improve the early strength of the castable, and an inlaid structure of aluminum silicate and the like and carbon raw materials is formed in the matrix, which can significantly optimize the slag resistance of the iron ditch castable at high temperature; in addition, the expanded graphite-silicon carbide whisker heterogeneous network structure significantly improves the high-temperature mechanical properties and the ability to resist thermal stress damage of the material.

[0032] 2. Furthermore, the present invention adopts microwave chemical vapor deposition to prepare EG-SiC, the preparation process is fast and efficient, the cost is low, and the silicon carbide whiskers are more evenly distributed on the surface of expanded graphite, which is conducive to giving full play to its performance improvement effect in the iron ditch castable. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is an electron microscope image of the preloaded expanded graphite obtained in Example 1.

[0034] Figure 2 This is an electron microscope image of the pre-synthesized EG-SiC obtained in Example 1.

[0035] Figure 3 This is an electron microscope image of the pre-synthesized EG-SiC obtained in Example 6. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is described in detail through the following embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0037] To avoid repetition, the materials involved in the specific implementation are first described as follows, and will not be repeated in the embodiments:

[0038] The content of Al2O3 in plate-like corundum is >99wt%, and the particle size of plate-like corundum is 1-0.1mm and <45μm.

[0039] The content of Al2O3 in the active α-Al2O3 micropowder is >99.5wt%, and the particle size of the active α-Al2O3 micropowder is <5μm.

[0040] The content of SiO2 in ordinary silicon micropowder is >95wt%, and the particle size of silicon micropowder is <0.5μm.

[0041] The content of high-purity silicon micropowder SiO2 is >99wt%, and the particle size is <0.5μm.

[0042] The SiC content in silicon carbide is >98wt%, including SiC fine powder and SiC particles. The particle size of the SiC particles is 1-0.1mm, and the particle size of the SiC micropowder is <75μm.

[0043] The content of Al2O3 in calcium aluminate cement is >70wt%, and the particle size of calcium aluminate cement is <45μm.

[0044] The carbon sources are presynthesized EG-SiC and spherical asphalt, and the particle size of the spherical asphalt is 1-0 mm.

[0045] The composite additive is a composite of at least two of boron carbide, elemental silicon powder, zirconium boride, metal aluminum powder and polycarboxylic acid dispersant.

[0046] The content of Al2O3 in brown corundum particles is >95wt%, and the particle sizes include 3-1mm, 5-3mm, and 8-5mm.

[0047] Example 1

[0048] Provided is a method for preparing an iron trough castable containing presynthesized EG-SiC, comprising the following steps:

[0049] 1) Preparation of pre-synthesized EG-SiC

[0050] Expanded graphite is placed on Ni 2+The catalyst-loaded expanded graphite slurry was obtained by ultrasonic stirring in a nickel acetate solution with a concentration of 0.1 mol / L for 20 minutes; the catalyst-loaded expanded graphite slurry was filtered and dried at 80°C for 12 hours to obtain preloaded expanded graphite. The preloaded expanded graphite was placed in the middle of a quartz tube, and then placed in the central reaction zone of a microwave reactor. A nitrogen vent pipe was inserted into a mixed solution of anhydrous ethanol and methylsilane (volume ratio of 2:1) heated to 80°C in a water bath, and the mixed steam was carried into the microwave reactor by nitrogen. The flow rate of nitrogen was controlled at 250 mL / min, and microwave heating was performed at a power of 900 W to 1100°C and kept for 30 minutes to obtain pre-synthesized EG-SiC.

[0051] 2) Weigh the raw materials:

[0052] Weigh 16wt% of plate-shaped corundum, 9wt% of composite micropowder, 16.4wt% of silicon carbide, 2wt% of calcium aluminate cement, 2wt% of spherical asphalt, 0.1wt% of explosion-proof fiber, 2.5wt% of composite additives, and 52wt% of brown corundum particles. Add 1wt% of the pre-synthesized EG-SiC obtained in step 1).

[0053] 3) The raw materials weighed in step 2) are mixed uniformly, 4.2 wt% of water accounting for the total amount of the raw materials is added and mixed uniformly, and then poured and vibrated to form.

[0054] The castable after the above molding is sequentially cured, dried and heat treated, and the performance test is performed; wherein:

[0055] 1) Curing process: curing at room temperature for 24 hours.

[0056] 2) Drying process: drying at 110°C for 24 hours.

[0057] 3) The heat treatment process is as follows: heat treatment at 1450℃ for 3h and test its cold compressive strength; calculate the compressive strength retention rate of the sample after 900℃ quenching test; test the high temperature flexural strength of the sample by keeping it at 1400℃ for 0.5h; use the static crucible method to keep it at 1550℃ for 3h and test the slag line erosion depth of the sample profile. The specific performance test results are shown in Table 1.

[0058] Figure 1 Expanded graphite loaded with catalyst, Figure 2 The EG-SiC is catalytically grown by the expanded graphite loaded with nickel ions at a concentration of 0.1 mol / L and treated at 1100°C. Figure 2 Display: A small amount of SiC whiskers are generated on expanded graphite.

[0059] Example 2

[0060] The specifics are the same as Example 1, except that the content of the pre-synthesized EG-SiC is 2 wt %. See Table 1 for specific performance test results.

[0061] Example 3

[0062] The specific method is the same as Example 2, except that the microwave heat treatment temperature is 1200° C. for 30 min, and the content of the pre-synthesized EG-SiC is 3 wt %. See Table 1 for specific performance test results.

[0063] Example 4

[0064] The specific embodiment is the same as Example 1, except that: Ni in the nickel acetate solution 2+ The concentration is 0.2 mol / L. See Table 1 for specific performance test results.

[0065] Example 5

[0066] The specific embodiment is the same as Example 2, except that: Ni in the nickel acetate solution 2+ The concentration is 0.2 mol / L. See Table 1 for specific performance test results.

[0067] Example 6

[0068] The specific embodiment is the same as Example 3, except that: Ni in the nickel acetate solution 2+ The concentration is 0.2 mol / L. See Table 1 for specific performance test results.

[0069] Figure 3 This is EG-SiC catalytically grown on expanded graphite loaded with nickel ions at a concentration of 0.2 mol / L and treated at 1200°C. The figure shows that a large number of SiC whiskers are generated on the expanded graphite.

[0070] Comparative Example 1

[0071] Provided is a conventional iron ditch castable and a preparation method thereof, comprising the following steps:

[0072] 1) Weigh the raw materials:

[0073] Weigh 16wt% of plate-shaped corundum, 9wt% of composite micropowder, 16.4wt% of silicon carbide, 2wt% of calcium aluminate cement, 2wt% of spherical asphalt, 0.1wt% of explosion-proof fiber, 2.5wt% of composite additives, and 52wt% of brown corundum particles;

[0074] 2) The raw materials weighed in step 1) are mixed uniformly, 4.2 wt% of water accounting for the total amount of the raw materials is added and mixed uniformly, and then poured and vibrated to form.

[0075] The molded castable was cured, dried and heat treated in sequence according to the method of Example 1, and a performance test was performed. The specific performance test results are shown in Table 1.

[0076] Table 1. Differences between Examples 1-6 and Comparative Example 1 and performance test results

[0077]

[0078] It can be seen from Table 1 that after the pre-synthesized EG-SiC is introduced into the iron trough castable, the mechanical properties and slag resistance of the material are significantly improved. Among them, with the increase of nickel ion concentration or the increase of microwave heat treatment temperature, it is conducive to catalytic growth to obtain more uniform EG-SiC, and the improvement of castable performance is more significant.

[0079] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solution and its improved conception within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. An iron trough castable containing pre-synthesized EG-SiC, characterized in that: The raw material composition is as follows: 10-17wt% of plate-shaped corundum, 7-13wt% of composite micropowder, 12-25wt% of silicon carbide, 1-3wt% of calcium aluminate cement, 1-3wt% of spherical asphalt, 0.1-0.2wt% of explosion-proof fiber, 2-5wt% of composite additives, and the balance is brown corundum particles; 1-3wt% of pre-synthesized EG-SiC is added; wherein: The pre-synthesized EG-SiC is nanometer silicon carbide whiskers grown in situ between worm-like expanded graphite sheet structures.

2. The iron ditch castable according to claim 1, characterized in that: The preparation of the pre-synthesized EG-SiC comprises the following steps: The expanded graphite is placed in a nickel acetate solution, dispersed by ultrasonic stirring, filtered and dried to obtain the expanded graphite loaded with a nickel acetate catalyst; the expanded graphite loaded with a nickel acetate catalyst is then placed in a microwave reactor, and a mixed vapor of anhydrous ethanol and methylsilane is carried into the microwave reactor by nitrogen gas to perform microwave heating reaction to prepare presynthesized EG-SiC.

3. The iron ditch castable according to claim 2, characterized in that: Ni in nickel acetate solution 2+ The concentration is 0.05-0.25mol / L.

4. The iron ditch castable according to claim 2, characterized in that: The drying process is: drying at 60-80°C for 8-12 hours; the ultrasonic stirring time is 15-30 minutes.

5. The iron ditch castable according to claim 2, characterized in that: The volume ratio of anhydrous ethanol to methylsilane is 1-2:

1.

6. The iron ditch castable according to claim 2, characterized in that: The microwave heating reaction was carried out at 1100-1200°C for 20-45 min.

7. The iron ditch castable according to claim 2, characterized in that: The microwave heating power is 700-1100 W; the flow rate of nitrogen is controlled at 200-500 mL / min.

8. The iron ditch castable according to claim 1, characterized in that: The Al2O3 content in the plate-like corundum is >99wt%, and the particle size includes 1-0.1mm and <45μm; the SiC content in the silicon carbide is >98wt%, and the particle size includes 1-0.1mm and <75μm; the Al2O3 content in the calcium aluminate cement is >70wt%, and the particle size is <45μm; the Al2O3 content in the brown corundum particles is >95wt%, and the particle size includes 3-1mm, 5-3mm, and 8-5mm; the spherical asphalt particle size is 1-0mm.

9. The iron ditch castable according to claim 1, characterized in that: The composite micropowder is a composite of two or more of ordinary silicon micropowder, high-purity silicon micropowder and active α-Al2O3 micropowder, wherein: the content of SiO2 in the ordinary silicon micropowder is >95wt%, and the particle size is <0.5μm; the content of SiO2 in the high-purity silicon micropowder is >99wt%, and the particle size is <0.5μm; the content of Al2O3 in the active α-Al2O3 micropowder is >99.5wt%, and the particle size is <5μm; the composite additive is a composite of at least two of boron carbide, elemental silicon powder, zirconium boride, metal aluminum powder, and polycarboxylic acid dispersant.

10. A method for preparing an iron trough castable containing presynthesized EG-SiC according to any one of claims 1 to 9, characterized in that: The following steps are involved: Plate-shaped corundum, composite micropowder, silicon carbide, calcium aluminate cement, presynthesized EG-SiC, spherical asphalt, explosion-proof fiber, composite additives and brown corundum particles are weighed and mixed evenly, 3-6wt% of water accounting for the total amount of raw materials is added and mixed evenly, and then poured and vibrated to obtain iron ditch castable.

Citation Information

Patent Citations

  • Carbon raw material for carbon composite refractory material and preparation method thereof

    CN103922760A

  • Preparation method of diamond-SiC composite substrate with adjustable thermal conductivity

    CN116121725A

  • Carbon material with uniform silicon carbide whiskers and preparation method thereof

    CN116695257A

  • In-situ silicon carbide whisker toughened iron runner castable and preparation method thereof

    CN117700239A

  • Anti-erosion Al2O3-SiC-C iron runner castable containing carbon black and graphite electrode powder and preparation method of anti-erosion Al2O3-SiC-C iron runner castable

    CN118359444A